2021
DOI: 10.1101/mcs.a006135
|View full text |Cite
|
Sign up to set email alerts
|

Somatic variation as an incidental finding in the pediatric next-generation sequencing era

Abstract: The methodologic approach used in next-generation sequencing (NGS) affords a high depth of coverage in genomic analysis. Inherent in the nature of genomic testing, there exists potential for identifying genomic findings that are incidental or secondary to the indication for clinical testing, with the frequency dependent on the breadth of analysis and the tissue sample under study. The interpretation and management of clinically meaningful incidental genomic findings is a pressing issue particularly in the pedi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 43 publications
0
2
0
Order By: Relevance
“…These patients showed different clinical manifestations such as opposite abnormal head circumference types, and microcephaly and macrocephaly. To identify the correlations between the different variations of PPP2R1A with clinical features, we collected and reviewed the clinical and genetic information of 64 NDD patients (2 reported fetuses were excluded, and 4 patients in our study were included) [ 7 , 10 , 13 , 14 , 15 , 22 ]. We found that patients with microcephaly often had brain structure abnormalities and severe epilepsy; patients with Met180Thr/Val variants displayed macrocephaly and severe ID, but did not suffer from epilepsy; patients with Arg258His/Ser variants all had microcephaly but rarely suffered from epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…These patients showed different clinical manifestations such as opposite abnormal head circumference types, and microcephaly and macrocephaly. To identify the correlations between the different variations of PPP2R1A with clinical features, we collected and reviewed the clinical and genetic information of 64 NDD patients (2 reported fetuses were excluded, and 4 patients in our study were included) [ 7 , 10 , 13 , 14 , 15 , 22 ]. We found that patients with microcephaly often had brain structure abnormalities and severe epilepsy; patients with Met180Thr/Val variants displayed macrocephaly and severe ID, but did not suffer from epilepsy; patients with Arg258His/Ser variants all had microcephaly but rarely suffered from epilepsy.…”
Section: Discussionmentioning
confidence: 99%
“…A genetic syndrome caused by pathogenic heterozygous variants in the PP2A subunits was first described in 2015, when 3 de novo PPP2R1A variants and 4 de novo PPP2R5D variants were identified among 1133 proband‐parent trio exomes in the United Kingdom's Deciphering Developmental Disorders project (Deciphering Developmental Disorders, 2015). Since that time, 39 patients have been reported with 19 different de novo PPP2R1A variants (Deciphering Developmental Disorders, 2015; Houge et al, 2015; Lenaerts et al, 2021; Melas et al, 2021; Ruxmohan et al, 2021; Wallace et al, 2019; Zhang et al, 2020). The associated phenotype is variable and includes intellectual disability, developmental delay, epilepsy, agenesis/dysgenesis of the corpus callosum, and dysmorphic facial features.…”
Section: Introductionmentioning
confidence: 99%